Seizing a Brighter Future for All : Former Yugoslav Republic of Macedonia Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
This Systematic Country Diagnostic (SCD) identifies three mutually reinforcing pathways for FYR Macedonia to sustainably accelerate growth, reduce poverty, and consolidate the middle class. An examination of the country’s progress in the 27 years of its independence reveals three strategic pathways for FYR Macedonia to overcome its development challenges and leverage new opportunities. The first is to foster a more dynamic and competitive private sector. The second is to build up human capital to be more competitive and adaptive and close opportunity gaps. And the third is to achieve sustainability through effective governance, fiscal prudence, and enhanced environmental management and resilience to natural hazards. Embarking on these strategic pathways would help sustain the robust and inclusive growth necessary to eliminate extreme poverty—a goal FYR Macedonia can achieve within the next decade—and promote shared prosperity. This SCD identifies short- and medium-term policy priorities to help FYR Macedonia achieve its long-term vision.